2015
DOI: 10.1523/jneurosci.0276-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Interspike Intervals Reveal Functionally Distinct Cell Populations in the Medial Entorhinal Cortex

Abstract: The superficial layers of the medial entorhinal cortex (MEC) contain spatially selective neurons that are crucial for spatial navigation and memory. These highly specialized neurons include grid cells, border cells, head-direction cells, and irregular spatially selective cells. In addition, MEC neurons display a large variability in their spike patterns at a millisecond time scale. In this study, we analyzed spike trains of neurons in the MEC superficial layers of mice and found that these neurons can be class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(111 citation statements)
references
References 41 publications
21
90
0
Order By: Relevance
“…Using these criteria, a large majority (~95 %) of mEC cells was classified as spatial (Figure 1A), including numerous cells which would previously have been identified as non-spatial (Figure S2C). The proportions of cells with specialized spatial firing patterns were comparable to previous reports (grid cells: 17.7 %; border cells: 9.3 %) (Kropff et al, 2015; Latuske et al, 2015; Tang et al, 2014; Zhang et al, 2013) (Figure S2D), but also included a substantial fraction of spatial cells (67.5 %) that lacked any grid or border pattern. We refer to the latter type as non-grid spatial cells (Figure 1B, C and Table S1) and confirmed that their spatial firing patterns did not arise from systematic variation in running speed.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Using these criteria, a large majority (~95 %) of mEC cells was classified as spatial (Figure 1A), including numerous cells which would previously have been identified as non-spatial (Figure S2C). The proportions of cells with specialized spatial firing patterns were comparable to previous reports (grid cells: 17.7 %; border cells: 9.3 %) (Kropff et al, 2015; Latuske et al, 2015; Tang et al, 2014; Zhang et al, 2013) (Figure S2D), but also included a substantial fraction of spatial cells (67.5 %) that lacked any grid or border pattern. We refer to the latter type as non-grid spatial cells (Figure 1B, C and Table S1) and confirmed that their spatial firing patterns did not arise from systematic variation in running speed.…”
Section: Resultssupporting
confidence: 88%
“…For mEC recordings, classification has previously been performed by first calculating descriptive values for each cell class (grid score, border score, spatial information, HD mean resultant length) and by then comparing the values to those calculated from the shuffled data of all recorded mEC cells pooled together (Figure S2A) (Barry et al, 2012; Bjerknes et al, 2015; Boccara et al, 2010; Koenig et al, 2011; Kropff et al, 2015; Krupic et al, 2015; Langston et al, 2010; Latuske et al, 2015; Perez-Escobar et al, 2016; Stensola et al, 2012; Tang et al, 2014; Wills et al, 2010; Winter et al, 2015; Zhang et al, 2013). However, pooling shuffled data across all cells fails to account for the firing statistics of individual cells, most notably the relationship between a cell’s firing rate and its spatial information (Figure S2B) (Rolls et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have identified a substantial subset of mEC cells as nonspatial (Kropff et al, ; Latuske et al, ; Tang et al, ; Tang et al, ; Zhang et al, ). In contrast, recent work utilizing more sophisticated classification criteria found that almost all mEC cells exhibit some degree of spatial firing (Diehl et al, ; Hardcastle, Maheswaranathan, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Including the entire entorhinal-hippocampal circuit A key objective for a more complete understanding of entorhinal-hippocampal function will be to determine how cell types with different functional correlates map onto the variety of morphological or neurochemical cell types and their unique connectivity patterns. Recent data suggest that, in layer II of MEC, both stellate and pyramidal cells can be grid cells, although stellate cells may comprise the majority of them 256,257,[272][273][274][275] . If so, are grid patterns created independently in these two cell classes, or does one of them inherit the grid from the other?…”
Section: Development Of Spatial Network Architecturesmentioning
confidence: 99%